Implementation of Epidemiological Investigations in Efforts to Eradicate DHF in the Kelay Community Health Center Working Area, Berau Regency - Anisya Dea Rizkita; Kresna Febriyanto; Ferry Fadzlul Rahman; Chorie Alivia Rahmadani Balby; Monica Yulansa Saputri (Faculty of Public Health, University of Jember in collaboration with PERSAKMI, 2023)
Abstract. Dengue Hemorrhagic Fever (DHF) is an acute viral infection caused by the dengue virus characterized by fever for 2-7 days accompanied by bleeding manifestations, decreased platelets (thrombocytopenia), and the presence of hemoconcentration, which is characterized by plasma leakage (increased hematocrit, ascites, pleural effusion, hypoalbuminemia). It may be accompanied by atypical symptoms, including headache, muscle and bone pain, skin rash, and pain behind the eyeball. Community service aims to conduct a survey of larva-free areas and distribute abate powder. Observation of all water reservoirs in people's homes is the method used for this activity. From 17 to 21 May 2022, this activity was conducted for five days. The community empowerment was held in the working area of the Kelay Community Health Center in Sido Bangen and Merasa Villages, Berau Regency, with a target of 227 houses and 5 RTs per region. On the 18th and 20th of May, 2022, a larval survey and the distribution of Abate powder were conducted. The larvae survey revealed ABJ (larvae-free rate) results of 67.65 percent in Feel Village and 81.32 percent in Sido Bangen Village. Seeing the low ABJ after the implementation of countermeasures, it is necessary to implement PSN (Eradication of Mosquito Nest) Plus through community mobilization.